Melatonin protects the central nervous system of rats against toluene-containing thinner intoxication by reducing reactive gliosis - Baydas, G; Reiter, RJ; Nedzvetskii, VS; Yasar, A; Tuzcu, M; Ozveren, F; Canatan, H (Elsevier Ireland Ltd, 2003)
Neuroprotective effects of melatonin against free radical damage have been studied extensively. Thinner containing 60-70% toluene is a neurotoxic mixture which is widely used as an aromatic industrial solvent. This product has been shown to cause functional and structural changes in the central nervous system. Toluene generates reactive oxygen species (ROS) and the toxic effects relating to these reactants. In the present study we investigated glial reactivity in hippocampus, cortex and cerebellum and the expression of glial fibrillary acidic protein (GFAP) after exposure of rats to toluene vapor (3000 ppm) for 45 days. We also examined the protective effects of melatoriin against gliosis. Western blots demonstrated a marked elevation in total GFAP, a specific marker for astrocytes, by thinner fume inhalation in the hippocampus (P < 0.001), cortex (P < 0.01) and cerebellum (P < 0.05) of rats. Melatonin administration prevented the increase of total GFAP induced by thinner fume inhalation. Thinner exposure caused a significant increase of lipid peroxidation products (malondialdehyde and 4-hydroxyalkenals) in all brain regions (P < 0.01 for each region), and this elevation was also was inhibited by melatonin. Furthermore, melatonin augmented glutathione levels in all brain regions (P < 0.05 for each region) investigated. In conclusion, melatonin treatment may provide neuroprotection against toluene neurotoxicity by increasing the survival of glial cells possibly by directly scavenging ROS and by indirectly augmenting their antioxidant capacity. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: toluene; glial fibrillary acidic protein; lipid peroxidation; melatonin; hippocampus; cortex